Hubungan Kadar TSH Terhadap Kadar FT4 Pada Pasien Tiroid Di Bangkalan - Ellies Tunjung Sari Maulidiyanti (THE JOURNAL OF MUHAMMADIYAH MEDICAL LABORATORY TECHNOLOGIST, 2018)
AbstractThyroid disorder disease ranks second most in the list of metabolic diseases after diabetes mellitus (DM). Thyroid disease or Thyroid abnormalities is a condition of abnormalities in a person due to the disorder of the thyroid gland. TSH is a primary factor that controls thyroid cell growth and synthesis also thyroid hormone secretion. TSH secretion is stimulated by low levels of T3 and T4 and by the hormone TRH (Thyroid Releasing Hormone) the hypothalamus is inhibited by elevated levels of T3 and T4. T3 and T4 are circulating in the plasma, most of which are bound with proteins, Thyroid Binding Globulin (TBG) and a small part in free form that are Free Triiodotironine (FT3) and Free Thyroxine (FT4). The free hormone (FT3 and FT4) is an actively metabolic fraction which is known to be quantitative. Currently the measurement of free hormone levels should be part of a complete examination of the status of the thyroid gland. The purpose analyzes the levels of TSH, FT4 and proves the relationship between the two in patients with thyroid disorders. This examination by using ELISA method is with EIA competitive principles and sandwiches. The samples are serum of patients with thyroid disorders at RSUD Bangkalan and Farmalab Laboratory from October to November 2017.The 30 samples obtaines an average result of TSH level of 1.9 mIU / L and an average FT4 level of 2.8 ng / dl. Next test Kolmogorov-Smirnov and Spearrman's test results obtained if the variable one value rose (high) then the other variable down (low). It can be concluded that there is an opposite relationship between TSH levels and FT4 levels, if TSH levels increase, the FT4 level decreases, and so it is also in contrast Keywords: TSH, FT4, thyroid disorders